Maintenance Analysis of Multi Mover M600U by Using Reliability Centred Maintenance Method - Sulistyo, Arif Budi; Saputra, Aji Eka (Universitas Al Azhar Indonesia, 2025)
PT XYZ is a manufacturing company that provides hot metal transportation handling services and supports Blast Furnace (BF) operations at the Krakatau Posco Plant using heavy equipment, namely Multi Mover M600U. To ensure smooth production processes, effective and efficient maintenance management of the heavy equipment are essential to enhance reliability. This study evaluates potential failure modes, their impacts and appropriate handling measures for the Multi Mover M600U using the Failure Mode and Effect Analysis (FMEA) method. The result of the study shows the highest Risk Priority Number (RPN) value of 350 in the Electrical PLC component, with a total RPN of 777 for the Electrical and Brake systems. These findings indicate that the Electrical and Brake systems have the highest failure rates due to downtime compared to other systems. Through the Reliability Centred Maintenance (RCM) approach, this study proposes a maintenance scheduling plan to minimize the risk of sudden downtimes, and their impacts on time and maintenance costs.Keywords - Downtime, Failure Mode and Effect Analysis, Heavy Equipment Maintenance, Reliability Centred Maintenance, Risk Priority Number.